Effects of plant sterols derived from Aloe vera gel on human dermal fibroblasts in vitro and on skin condition in Japanese women - Tanaka M; Misawa E; Yamauchi K; Abe F; Ishizaki C (Dove Medical Press, 2015)
Miyuki Tanaka,1 Eriko Misawa,1 Koji Yamauchi,1 Fumiaki Abe,1 Chiaki Ishizaki2 1Functional Food Research Department, Food Science and Technology Institute, Morinaga Milk Industry Co, Ltd, Zama, Kanagawa, 2Ebisu Skin Research Center, Inforward, Inc., Tokyo, Japan Background: Aloe is known for its topical use for treating wounds and burns. Many previous studies reported the healing effects of Aloe vera. However, there are few clinical studies on the effect of orally administered A. vera gel on the skin. Aloe sterols are a type of plant sterols that have the capability to regulate the metabolism of glucose and lipids. In a recent study, we confirmed that ingested Aloe sterols reached the peripheral tissues through the bloodstream. However, their influence on dermal fibroblasts has not been investigated. Methods: First, we investigated the capability of Aloe sterols (cycloartenol and lophenol) to stimulate human dermal fibroblasts in vitro. Then, we investigated the effect of intake of Aloe vera gel powder (AVGP) containing 40 µg Aloe sterols on the skin conditions in Japanese women with dry skin in a randomized, double-blind, placebo-controlled trial. Results: After cocultivation with Aloe sterols, the production of collagen and hyaluronic acid increased by approximately two-fold and 1.5-fold, and gene expression levels of these enzymes responsible for their synthesis were also observed in human dermal fibroblasts. An increase in arm skin hydration was observed at 8 weeks in the AVGP group, whereas a slight decrease in arm skin hydration was noted in the placebo group. However, there was no statistical difference between AVGP and placebo groups in skin moisture. In subgroup analysis, the change in the mean wrinkle depth was significantly lower in the AVGP group than in the control group. In addition, percent body fat after 8 weeks was significantly lower in the AVGP group. No AVGP intake-dependent harmful phenomenon was observed during the intake period. Conclusion: The present study confirms that daily oral Aloe sterol-containing AVGP significantly reduced facial wrinkles in women aged ≥40 years, and Aloe sterols stimulate collagen and hyaluronic acid production by human dermal fibroblasts. Keywords: aloe sterol, collagen, wrinkle